2019
DOI: 10.1186/s12879-019-3995-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and associated factors of HSV-2 infection among general population in Shandong Province, China

Abstract: Background Herpes simplex virus type-2 (HSV-2) infection is the main cause of genital ulcer disease and increases the risk of HIV acquisition. Little information is available regards the epidemiological characteristics of HSV-2 among general population in China. The aim of this study was to explore seroprevalence and associated factors of HSV-2 and provide information for design of HSV-2 control strategy in Shandong, China. Methods In this cross-sectional study, a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
7
3
Order By: Relevance
“…These studies had approximately 2.5-10 times lower HSV-2 seroprevalence compared to Nigeria. Also, contrary to the findings of many studies [27,[30][31][32][33], it was found that seroprevalence of HSV-2 was higher in males compared to females in Nigeria, but this observation should be interpreted with caution as only 3 studies with a total sample population of 14 were used to estimate the seroprevalence of HSV-2 among Nigerian males and as such the disparity may be due to sparseness of seroprevalence data amongst the Nigerian male population. The seroprevalence of 57.5% among HIV-infected patients is in tandem with the established trend of risk association between HSV-2 and HIV [34].…”
Section: Discussioncontrasting
confidence: 74%
“…These studies had approximately 2.5-10 times lower HSV-2 seroprevalence compared to Nigeria. Also, contrary to the findings of many studies [27,[30][31][32][33], it was found that seroprevalence of HSV-2 was higher in males compared to females in Nigeria, but this observation should be interpreted with caution as only 3 studies with a total sample population of 14 were used to estimate the seroprevalence of HSV-2 among Nigerian males and as such the disparity may be due to sparseness of seroprevalence data amongst the Nigerian male population. The seroprevalence of 57.5% among HIV-infected patients is in tandem with the established trend of risk association between HSV-2 and HIV [34].…”
Section: Discussioncontrasting
confidence: 74%
“…Therefore, improving HSV-2 related knowledge and the frequency of condom use is an effective method to prevent and control HSV-2 infection and transmission among MSM in Shenzhen. Most studies demonstrated that having multiple sex partners is associated with HSV-2 infection [ 31 , 32 ]. Although FAC3_1 (X 8 = Number of male sex partners in P6M) was not associated with HSV-2 infection in this study, it is necessary to prevent and control HSV-2 infection in MSM with multiple sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among pregnant women in rural regions of India have shown a lower seroprevalence of HSV-2 relative to studies in a given region [24]. Other studies originating in China have also shown that the seroprevalence of HSV-2 was higher in individuals from the eastern region and urban areas of Shandong than those from other regions [25]. The other large epidemiological study on the occurrence of HSV in the Polish population covering 4 regions reported geographical place of residence as a significant risk factor for HSV-2 seropositivity [26].…”
Section: Discussionmentioning
confidence: 88%